2012
DOI: 10.3340/jkns.2012.52.4.339
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Patterns and Risk Factors of Newly Developed Vertebral Compression Fractures after Percutaneous Vertebroplasty

Abstract: ObjectiveThe purpose of this study was to investigate the patterns and the risk factors of newly developed vertebral compression fractures (VCFs) after percutaneous vertebroplasty (PVP).MethodsWe performed a retrospective review of the 244 patients treated with PVP from September 2006 to February 2011. Among these patients, we selected 49 patients with newly developed VCFs following PVP as the new VCFs group, and the remaining 195 patients as the no VCFs group. The new VCFs group was further divided into 2 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
1
19
2
Order By: Relevance
“…9 Similar to other reported results, 17 the overall incidence of NVCF in our study was 17.2% over 4 years. The risk of NVCF increases yearly as time passes; however, in our study, adjacent fractures mainly occurred within 2 years, whereas remote fractures occurred at a consistent rate every year.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9 Similar to other reported results, 17 the overall incidence of NVCF in our study was 17.2% over 4 years. The risk of NVCF increases yearly as time passes; however, in our study, adjacent fractures mainly occurred within 2 years, whereas remote fractures occurred at a consistent rate every year.…”
Section: Discussionsupporting
confidence: 91%
“…13,17,20,21 In our study, lower BMD was a risk factor of NVCF as shown by univariate and multivariate analysis and, in particular, a lower BMD is related to the risk of remote fractures (Table 5). In the NVCF group, the average BMD decreased from À 3.29 to À 4.1 compared with the control group (P = 0.55) (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…After reviewing the full text of the remaining 26 studies, we excluded nine additional full‐text articles. Finally, 17 unique studies with sufficient data were included and analysed in the meta‐analysis . A flow diagram that shows the literature search process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The descriptive statistics for the studies that were included in our meta‐analysis are summarized in Table . Of the studies, eight were conducted in China, six were conducted in Korea, one was conducted in the Netherlands, one was conducted in Japan and one was conducted in Spain . The results of the quality assessment are summarized as follows: two studies received a score of 9, eight studies received a score of 8, five studies received a score of 7 and two studies received a score of 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation